EXPERT SYSTEM FOR DIAGNOSING DISEASES IN DOGS BASED ON WEB USING DEMPSTER-SHAFER METHOD - Nalle, Olsen Junior; Sina, Derwin Rony; Ledoh, Juan Rizky Mannuel (Jurnal Transformatika, 2024)
In the study titled " Expert System For Diagnosing Diseases In Dogs Based On Web Using Dempster-Shafer Method " it was found that keeping dogs provides positive benefits to human mental health. Despite dogs having rapid adaptability, high loyalty, as well as significant development and intelligence, proper care is essential to maintain their health and prevent diseases. The limitation in the number of veterinary doctors poses a challenge in handling animal diseases, particularly in dogs. Hence, this research utilizes an Expert System with the Dempster-Shafer method to diagnose canine diseases. Out of 45 test cases used to evaluate the system, it achieved an accuracy rate of 88.89% in comparison to veterinary doctors' diagnoses. Some cases showed discrepancies due to related symptoms, accounting for 11.11%, with more than one disease type within the system and having a confidence level below 70%.